A Meta-Analysis of Product Visual Aesthetics - Peng, Chenming; Eisend, Martin; Chen, Zengxiang (Journal of Marketing, 2026)
Despite firms’ emphasis on product visual aesthetics (PVA) for competitive advantage, questions remain regarding which aesthetic properties enhance PVA the most, the strength of PVA's effect on consumer responses, and moderating factors. To address these gaps, the authors conduct a meta-analysis of 727 effect sizes from 263 independent samples spanning 1993–2024. Findings reveal that both organizational and meaningful aesthetic properties positively impact PVA, and harmony is the strongest property. PVA positively influences both consumer attitudes and behaviors. The authors develop a comprehensive framework of moderators across five key groups: brand, product, communication, consumer, and environmental factors. The moderator analyses yield multiple important insights and (1) identify economic growth and consumption publicity as particularly influential, (2) recognize previously unexplored but relevant moderators (e.g., aesthetic object type, individualism, and income inequality), (3) clarify debated moderators (e.g., brand familiarity, product quality level, and gender), (4) reveal that certain moderator combinations can turn PVA effects negative (e.g., focusing on packaging aesthetics with utilitarian, private, nondurable, and low-quality products can turn the effect of PVA on attitudes negative), and (5) find an attitude–behavior gap in the moderating effects of PVA. The study provides new insights into the nuanced effects of PVA for effective application.